Implementation of the Smart & Green Building Concept in the UMY Student Dormitory Building - Sukamta, Sukamta; Jamal, Agus; Utama, Nafi Ananda; Suryanto, Rudy; Subandono, Bagus; Budiyanto, Gunawan; Suryanto, Arwan (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
The design of student housing in the modern era is not only required to provide functional comfort but also to address the challenges of energy efficiency and environmental sustainability. Universitas Muhammadiyah Yogyakarta (UMY) responds to these needs through the development of a Student Dormitory that adopts the principles of smart and green building. The purpose of this community engagement program is to evaluate the implementation of intelligent and environmentally friendly building concepts from technical, functional, and operational economic perspectives. This program employs a case study method with a descriptive qualitative approach, based on the analysis of building technical documents and a review of relevant national and international scientific literature. The findings show that the integration of digital access control systems (smart access), energy-efficient VRV (Variable Refrigerant Volume) cooling, harmonic filters, solar water heaters, and the use of Panasap Blue Glass has significantly contributed to reducing energy consumption by up to 40%. In addition to enhancing residents’ comfort and security, these technologies also demonstrate potential investment payback within 5 to 7 years. The implications extend beyond cost and operational efficiency, contributing directly to the achievement of the Sustainable Development Goals (SDGs). Furthermore, this program is grounded on the principle of sustainability, emphasizing the long-term utilization of eco-friendly technologies, the principle of benefit, ensuring tangible advantages for students, the university, and the wider community through improved quality of life and reduced carbon footprint; and the principle of economic viability, guaranteeing operational cost efficiency and financial sustainability of the project. The strategic objectives of this community engagement initiative are (1) to establish UMY’s Student Dormitory as a model of environmentally conscious student housing in tropical regions, (2) to promote knowledge and technology transfer on smart and green buildings to other universities, (3) to strengthen UMY’s reputation as a modern campus aligned with the SDGs agenda, and (4) to create an energy-efficient housing ecosystem that contributes to long-term cost savings and improved residents’ well-being. In conclusion, the study indicates that UMY’s student housing model, based on smart and green building principles, is feasible to adopt as a reference for dormitory development in other higher education institutions, particularly in tropical areas